Predicting the Viscosity of Non‐Newtonian Water‐in‐Oil Emulsions Based on the Lederer Model. Issue 2 (15th January 2019) - Shi, Shuqiang; Wang, Yongqing; Liu, Yonghui; Wang, Lei
Abstract: The accurate prediction of the viscosity of emulsions is highly important for oil well exploitation. Commonly used models for predicting the viscosity of water‐in‐oil (W/O) emulsions composed by two or three factors cannot always fit well the viscosity of W/O emulsions, especially in the case of non‐Newtonian W/O emulsions. An innovative and comprehensive method for predicting the viscosity of such emulsions was developed based on the Lederer, Arrhenius, and Einstein models, using experimental data. Compared with the commonly applied W/O emulsion viscosity models, the proposed method considers more factors, including temperature, volume fraction of water, shear rate, and viscosity of the continuous (oil) and dispersed phase (water). Numerous published data points were collected from the literature to verify the accuracy and reliability of the method. The calculation results prove the high accuracy of the model. Abstract : The viscosity of non‐Newtonian water‐in‐oil emulsions is a key parameter in heavy oil production, transportation, and operation design. Existing models for predicting the viscosity of such emulsions and experiments on their rheology are reviewed. A more comprehensive method was developed which considers more factors, including water content, temperature, shear rate, and viscosity of oil and water.